PENGARUH LITERASI KEUANGAN, PERILAKU KEUANGAN, GAYA HIDUP HEDONISME DAN KONTROL DIRI TERHADAP KEPUTUSAN INVESTASI PADA MAHASISWA UNIVERSITAS PANCASAKTI TEGAL - Wahyudi, Catur; Wartoyo (Jurnal Nusa Manajemen, 2025)
The aim of this study is to find out whether financial literacy, financial behavior, lifestyle hedonism and self-control influence sharia investment decisions either partially or simulta neously in students of Pancasakti Tegal University. It is hoped that this research could be a reference as well as a benefit to enhance an investment decision in students. This research uses quantitative methods. The population in this study is Students of Pancasakti Tegal University with a total of 6,140 Students, while the sample in this research is 100 respondents. Data collection techniques used are observation methods, questionnaires and. The instrumental tests of this research include validity tests, reliability tests, classical assumptions tests, and hypothesis tests. The analytical techniques used are double linear analysis. The research results prove that there is an influence between the financial literacy variable of 3,256 and the t table of 1.985, meaning tcount > ttable (3,256> 1.984) so ​​that it influences sharia investment decisions, the financial behavior variable is 2.321 and the ttable is 1.985, meaning tcount > ttable ( 2,321> 1.984) so ​​that Ho is rejected and influences sharia investment decisions and hedonistic lifestyles is 1.197 and t table is 1.985, meaning tcount > ttable (1.197> 1.984) so ​​that Ho is accepted so it has no effect on sharia investment decisions, self control variable is 2.723 and ttable is 1.985 means tcount > ttable (2.723 > 1.984) so ​​Ho rejected so that it influences sharia investment decisions and financial literacy, financial behavior, hedonistic lifestyle and self-control Simultaneous positive influence on sharia investment decisions among students at Pancasakti University, Tegal.